2012
DOI: 10.3109/00207454.2012.700661
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Attenuation of Early Brain Dysfunctions Is Partially Related to its Inverting Acute Vasospasm in a Cisterna Magna Subarachnoid Hemorrhage (SAH) Model in Rats

Abstract: Subarachnoid hemorrhage (SAH)-induced brain injury is highly related to neurological deficits and mortality. Regional cerebral blood flow (rCBF) changes and vasoconstriction are two complications that occur soon after SAH experimentally. In this study we investigated the changes in rCBF and vertebro-basilar arterial diameter in a cisterna megna SAH model in Sprague-Dawley rats and intended to explore whether improving early rCBF reduction and cerebral vasospasm could contribute to alleviating blood-brain barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Intravenous administration of nimodipine five minutes after SAH improves circulation and attenuates vasospasm in rats [54]. Nicardipine (dihydropyridine) pellets positioned next to the basal arteries have been shown to reduce the occurrence of angiographic vasospasm in a dose-dependent manner in patients suffering from SAH [55, 56].…”
Section: Changes In Ion Channel Expression and Function In Delayedmentioning
confidence: 99%
“…Intravenous administration of nimodipine five minutes after SAH improves circulation and attenuates vasospasm in rats [54]. Nicardipine (dihydropyridine) pellets positioned next to the basal arteries have been shown to reduce the occurrence of angiographic vasospasm in a dose-dependent manner in patients suffering from SAH [55, 56].…”
Section: Changes In Ion Channel Expression and Function In Delayedmentioning
confidence: 99%
“…2,19 Therefore, early improvement of hypoxia by increasing cerebral blood flow or reducing vasospasm with nimodipine may contribute to decreased brain injury and safeguard neurons. 5,6 As mentioned earlier, IV nimodipine delivered higher concentrations of nimodipine in plasma, neuron, and cerebrospinal fluid than oral. Therefore, early treatment with IV nimodipine might have the potential to reduce severity of vasospasm after aSAH and decrease DCI occurrence better than oral nimodipine treatment.…”
Section: Discussionmentioning
confidence: 82%
“…5 Nimodipine decreased rat brain ischemia by improving cerebral blood flow, then reducing vasospasm to mitigate blood-brain barrier injury. 6 Moreover, the British Aneurysm Nimodipine Trial compared clinical outcomes following aSAH between oral nimodipine treatment within 96 hours and placebo. 7 This demonstrated that nimodipine produced significantly better outcomes, with 34% lowering of cerebral infarction and 40% poor outcome diminution.…”
Section: Introductionmentioning
confidence: 99%
“…1 Vasospasm was detected immediately after SAH (30 mins) but not thereafter, indicating that vasospasm is transient in this mild SAH model. Previous studies using ex vivo arteries 4143 and in vivo angiography 44,45 in relatively more severe SAH models have detected vasospasm. Specifically, an MRI study of a SAH model by puncturing the vessel found narrowing of vessels but vasoconstriction only reached significance in the right proximal ICA in the acute phase and returned to normal on day 9.…”
Section: Discussionmentioning
confidence: 98%